Utilization of immediate postpartum intrauterine device and its associated factors among women who gave birth in public hospitals in West Wollega Zone, Oromia, Ethiopia - Guye, Ararso Hordofa; Kanea, Efa Bayissa; Nigussie, Tadesse; Girma, Derara; Shambi, Dame Banti (Frontiers in Medicine, 2023)
Background: Immediate postpartum intrauterine device utilization during the postpartum period helps women to realize the desire to space births and prevent unplanned pregnancy. But many mothers do not get immediate postpartum family planning in developing countries, including Ethiopia. This increases the risk of unplanned pregnancy and pregnancy-related complications.Objective: To assess the immediate postpartum intrauterine device utilization and associated factors among women who gave birth in public hospitals in the West Wollega Zone, 2022.Methods: Institutional-based cross-sectional study was conducted in public hospitals in the West Wollega Zone among 605 postpartum mothers from April 15 to May 15, 2022. A systematic random sampling technique was used to select study subjects and the data were collected using an interviewer-administered structured questionnaire, which was then entered into epi-data version 4.6 and exported to the Statistical Package for Social Science version 26 for analysis. The variable with a p-value of < 0.05 with an adjusted odds ratio and a 95% confidence interval was used to declare statisticaly significant association.Result: Utilization of the immediate postpartum intrauterine device among respondents who gave birth in West Wollega public hospitals within 48 hours was 27.2% (95% CI: 23.7-30.9).